MORPHOLOGICAL AND MECHANICAL PROPERTIES OF MT. KELUD VOLCANIC ASH REINFORCED POLYESTER AND EPOXY COMPOSITES - Henny Pratiwi (Jurnal Teknik Mesin, 2017)
The use of suitable waste products as raw materials has become an interesting matter in composite industry nowadays due to the environmental issues. Volcanic ash is one of the waste materials containing a high number of silica. The aim of this study is to examine the morphological and mechanical properties of Mt. Kelud volcanic ash reinforced polyester and epoxy composites. The volcano ash was dried and sieved into 50 mesh then mixed with polyester or epoxy manually for 10 minutes. The ash added into the matrix was varied by 0%, 10%, 20%, 30% and 40% from matrix volume content. For epoxy matrix, the composite with 40 vol. % particles has the highest tensile strength. However, for the polyester/ash composites, the tensile strength continues to decrease with the addition of particles. There is a significant increasing of 47.04 % for polyester and 5.62 % for epoxy in impact strength when 40 vol. % of volcanic ash added into both polymers. The Scanning Electron Microscopy result shows that there is void and agglomeration contained in epoxy/ash composites and crack propagation along the surface of polyester/ash composites that could be the cause of the failure.